ETHNO-MEDICINAL AND ANTIMICROBIAL SCREENING OF BACOPA MONNIERI ( L.) PENNELL - Verma, Maya (Journal of Phytology, 2015)
The present study evaluates the ethno-medicinal importance and anti-microbial activity of Bacopa monnieri ( L.), a creeping herb, belonging to Scrophulariaceae against selected bacterial strains (Â  E.coli,E.coli K 88,Klebsiella pneumoniae,Proteus vulgaris,Bacillus subtilis UCÂ  564,B.pumilus 8241,B.licheniformis,Staphylococcus aureus ATCC 6571,Streptococcus faecalis 52,Enterococcus faecalis ATCC 29212,Pseudomonas aeruginosa,Salmonella typhii 62,Shigella dysenteriae 3,S.flexneri E0 3429,S.sonnei E0 8869 ) and fungal cultures of Aspergillus niger and candida albicans.